Creative Thought and the Divine Word: An Examination of the Mythological Expression of Cosmic Consciousness - Gunaltay Basak, Merve; Kocak, Aynur (MDPI, 2026)
This article adopts a comparative mythology framework in order to situate creation myths within a broad cultural context. It examines how different societies conceptualize the emergence of the universe through the interconnected notions of thought and word. The study demonstrates that, despite cultural diversity, these narratives articulate shared principles concerning the mental and linguistic foundations of existence while preserving tradition-specific expressions. The analysis is based on qualitative content analysis of primary mythological texts drawn from Hindu, Maori, Maya, Maiana, Dogon, Polynesian, Ancient Egyptian, and Turkish traditions, encompassing sources ranging from the Rig Veda and the Popol Vuh to the theology of Ptah and Dogon doctrines of word-based creation. These materials were examined through hermeneutic reading practices and comparatively evaluated using concept-oriented analytical categories. The findings indicate that cosmogonic myths operate beyond mere narrative description by structuring coherent models of creation in which cognitive intention and verbal articulation play constitutive roles.
Keywords: divine thought; sacred word; creation; God; mythology; Religion